2020
DOI: 10.30773/pi.2020.0189
|View full text |Cite
|
Sign up to set email alerts
|

How Do Children with Autism Spectrum Disorder Encode and Reproduce Visuospatial Stimuli?: Investigation into Visuospatial Processing Abilities and Styles

Abstract: Objective The purpose of this study was to examine the visuospatial processing abilities of children with autism spectrum disorder (ASD) using the Rey Osterrieth Complex Figure (ROCF).Methods One-hundred thirty-four children with ASD [mean age (MA)=113.56 months], 150 siblings of children with ASD (MA= 111.67 months), and 55 typically developing (TD) children (MA=109.02 months) were included in this study. During their one-time visit, participants completed the ROCF, various autism diagnostic assessments, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…This dichotomy does not appear to be unique to the auditory system, as children with ASD show comparable neural and behavioral signatures in discriminating first-order (e.g., luminance-defined) visual stimuli, but perform worse than TD controls in discriminating second-order (e.g., texture-defined) stimuli (Rivest et al 2013). Children with ASD have also been shown to trend toward local processing requirements in embedded figure (Manjaly et al 2007) and visual construction tasks (Kim et al 2020). These abnormalities in auditory and visual pattern formation are likely to play a key contributory role to the well-established difficulties in higher-order cognitive processes that accompany autism, such as the core symptom of impaired social communication.…”
Section: Autism Spectrum Disordermentioning
confidence: 99%
“…This dichotomy does not appear to be unique to the auditory system, as children with ASD show comparable neural and behavioral signatures in discriminating first-order (e.g., luminance-defined) visual stimuli, but perform worse than TD controls in discriminating second-order (e.g., texture-defined) stimuli (Rivest et al 2013). Children with ASD have also been shown to trend toward local processing requirements in embedded figure (Manjaly et al 2007) and visual construction tasks (Kim et al 2020). These abnormalities in auditory and visual pattern formation are likely to play a key contributory role to the well-established difficulties in higher-order cognitive processes that accompany autism, such as the core symptom of impaired social communication.…”
Section: Autism Spectrum Disordermentioning
confidence: 99%
“…Several causes could be responsible for their diverse behavioral presentation, and the distinct anomalous social visual attention pattern is a relevant issue yet to be explored in depth [67]. Patients with ASD have shown local processing preference on encoding visual information, and had difficulty in adopting chunking strategies to integrate the visual details [68][69][70]. Meanwhile, meta-analysis indicated that using a visual reminder, as a form of compensatory processing, may help to improve memory encoding and further enhance visual memory competence [71].…”
Section: Transdiagnostic Features Of Face Memory In Children With Asd and Adhdmentioning
confidence: 99%